Reversed synaptic effects of hypocretin and NPY mediated by excitatory GABA-dependent synaptic activity in developing MCH neurons - Li, Ying (American Physiological Society, 2013)
In mature neurons, GABA is the primary inhibitory neurotransmitter. In contrast, in developing neurons, GABA exerts excitatory actions, and in some neurons GABA-mediated excitatory synaptic activity is more prevalent than glutamate-mediated excitation. Hypothalamic neuropeptides that modulate cognitive arousal and energy homeostasis, hypocretin/orexin and neuropeptide Y (NPY), evoked reversed effects on synaptic actions that were dependent on presynaptic GABA release onto melanin-concentrating hormone (MCH) neurons. MCH neurons were identified by selective green fluorescent protein (GFP) expression in transgenic mice. In adults, hypocretin increased GABA release leading to reduced excitation. In contrast, in the developing brain as studied here with analysis of miniature excitatory postsynaptic currents, paired-pulse ratios, and evoked potentials, hypocretin acted presynaptically to enhance the excitatory actions of GABA. The ability of hypocretin to enhance GABA release increases inhibition in adult neurons but paradoxically enhances excitation in developing MCH neurons. In contrast, NPY attenuation of GABA release reduced inhibition in mature neurons but enhanced inhibition during development by attenuating GABA excitation. Both hypocretin and NPY also evoked direct actions on developing MCH neurons. Hypocretin excited MCH cells by activating a sodium-calcium exchanger and by reducing potassium currents; NPY reduced activity by increasing an inwardly rectifying potassium current. These data for the first time show that both hypocretin and NPY receptors are functional presynaptically during early postnatal hypothalamic development and that both neuropeptides modulate GABA actions during development with a valence of enhanced excitation or inhibition opposite to that of the adult state, potentially allowing neuropeptide modulation of use-dependent synapse stabilization.